1992
DOI: 10.1177/0013164492052002006
|View full text |Cite
|
Sign up to set email alerts
|

An Exhaustive Examination of the Replicable Factor Structure of the Maslach Burnout Inventory

Abstract: Three-factor first order analyses have been used in the most successful of previous attempts to define the factor and subscale structures of the Maslach Burnout Inventory. It is suggested in the present paper that although a three factor structure has been shown to be the most readily replicable, this result does not exhaust the number of possible replicable factors in the Inventory. Using six independent sets of data drawn from previous studies involving a variety of subjects, the present analysis revealed th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
44
0
4

Year Published

2001
2001
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 56 publications
(49 citation statements)
references
References 24 publications
1
44
0
4
Order By: Relevance
“…For one thing, the Structural Equation Modeling (SEM) technique became increasingly widespread, facilitating the conduct of Confirmatory Factor Analyses (CFA), which in turn contributed to a massive (e.g. Cordes, Dougherty & Blum, 1997;Green, Walkey & Taylor, 1991;Holland, Michael & Kim, 1994;Lee & Ashforth, 1990;Schaufeli & van Dierendonck, 1993;Schutte, Toppinen, Kalimo & Schaufeli, 2000;Söderfeldt, Söderfeldt, Warg & Ohlson, Taris, Schreurs & Schaufeli, 1999;Walkey & Green, 1992) investigation of construct validity of the MBI. The bulk of research supports the three-factor representation of the MBI as well as convergent and discriminant validity of the instrument (see Maslach & Jackson, 1981;Meier, 1984;Schaufeli & Enzmann, 1998), however some ambiguity with respect to the factor structure and reliabilities of mainly the depersonalization subscale remain.…”
Section: A Assessing Burnoutmentioning
confidence: 99%
See 1 more Smart Citation
“…For one thing, the Structural Equation Modeling (SEM) technique became increasingly widespread, facilitating the conduct of Confirmatory Factor Analyses (CFA), which in turn contributed to a massive (e.g. Cordes, Dougherty & Blum, 1997;Green, Walkey & Taylor, 1991;Holland, Michael & Kim, 1994;Lee & Ashforth, 1990;Schaufeli & van Dierendonck, 1993;Schutte, Toppinen, Kalimo & Schaufeli, 2000;Söderfeldt, Söderfeldt, Warg & Ohlson, Taris, Schreurs & Schaufeli, 1999;Walkey & Green, 1992) investigation of construct validity of the MBI. The bulk of research supports the three-factor representation of the MBI as well as convergent and discriminant validity of the instrument (see Maslach & Jackson, 1981;Meier, 1984;Schaufeli & Enzmann, 1998), however some ambiguity with respect to the factor structure and reliabilities of mainly the depersonalization subscale remain.…”
Section: A Assessing Burnoutmentioning
confidence: 99%
“…Although most studies have supported the notion that the MBI captures a threedimensional representation of burnout, a number of studies have indicated that a two-factor representation was superior to the three-factor representation (e.g. Green, Walkey & Taylor, 1991;Holland, Michael & Kim, 1994;Schaufeli & van Dierendonck, 1993, Walkey & Green, 1992. Previous exploratory factor analysis of a Swedish version of the MBI-HSS (Söderfeldt, 1997) concluded that burnout was best represented by only two of Maslach's dimensionsemotional exhaustion and depersonalization.…”
Section: 1a Study I -Study Aimsmentioning
confidence: 99%
“…The result clearly supported the 3 factors structure of burnout. Other studies have found a 2 factor structure (19)(20)(21)(22), while a 4 factor structure has been showed by other researchers (23)(24)(25)(26). According to these research results, it can be concluded that burnout is a complex phenomenon with a multi-factorial structure.…”
Section: Research and Theoretical Frameworkmentioning
confidence: 55%
“…Obviously, personal accomplishment is a concept relatively unrelated to emotional exhaustion and depersonalization, as perceived by Walkey and Green (1992). As research suggests that personal accomplishment diminishes first when burnout develops, further research could focus on factors that are connected with this concept.…”
Section: Discussionmentioning
confidence: 99%